EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE STRUCTURED NUMBERED HEADS (SNH) PADA PEMAHAMAN KONSEP SISWA KELAS VII SMP NEGERI SURAKARTA DITINJAU DARI KECEMASAN SISWA PADA MATERI POKOK BANGUN DATAR - Hapsari, Alfonsa Maria Sofia (Widya Wacana: Jurnal Ilmiah, 2016)
This research aims at determining the effect of learning models on conceptual understandingviewed from the anxiety on mathematics. The learning models compared were SNH and directinstruction. This research used the quasi experimental research method.The proposed hypotheses of research were tested by using the two-way Anava with unbalancedcells. The results of research are as follows: 1) the cooperative learning model of the SNH typegives a better conceptual understanding the direct learning model; (2) the students with thelow anxiety level on Mathematics have a better conceptual understanding than those with themoderate anxiety level on Mathematics, and those with high anxiety level on Mathematics, andthe students the moderate anxiety level on Mathematics have a better conceptualunderstanding than those with the high anxiety level on MathematicsKeywords :Learning model, structured number heads.